ILRI medium-term plan 2008-2010. Livestock: a pathway out of poverty - International Livestock Research Institute (International Livestock Research Institute, 2007)
This document summarizes the content of ILRI’s Medium Term Plan (MTP) 2008-10. The key components are: 1. ILRI’s strategic directions 2. What are the main changes proposed, compared to the previous MTP (2006)? 3. What are the drivers of these changes and the rationale for new approaches? 4. How does ILRI’s 2008-2010 research portfolio align with the CGIAR system priorities? 5. highlights of the 2008 -2010 research portfolio. ILRI’s strategy is to make livestock a pathway out of poverty. It aims to achieve three outcomes: Securing assets to reduce vulnerability; increasing productivity to improve livelihoods; increasing incomes by enhancing market competitiveness and access. To implement this strategy, ILRI has organized its research program around four inter-related and output-focused themes (MTP Projects), which are: ‘Targeting and Innovation’ (identifying opportunities, setting priorities, understanding innovation systems); ‘Market Opportunities’ (enhancing market success of the poor); ‘Biotechnology’ (biosciences and bioinformatics for animal health and genetics); ‘People, Livestock and the Environment’ (natural resource solutions in livestock systems). ILRI also coordinates the CGIAR Systemwide Livestock Program (SLP) and the emerging plans for collective action by the Alliance of CGIAR centers and their partners in eastern and southern Africa. ILRI also brings a livestock perspective to several other CGIAR system initiatives. Other topics of discussions include; key global livestock issues; livestock and human health; vaccines and diagnostics; livestock genetics and breeding; research services; and ILRI ICRAF alignment in corporate services. The last section looks into lessons learned 2006–07; EPMR recommendations and ILRI’s responses to the recommendations; programmatic achievements and lessons learned in implementing the strategy; and key operating principles and practices.